Ovarian and Renal Vein Thrombosis: A Rare Cause of Fever Outer the Postpartum Period - Turhan Togan; Hale Turan; Egemen Cifci; Ceylan Çiftci (Hindawi Limited, 2015)
Although there is no other underlying disease, women can sometimes experience rare and serious diseases such as ovarian vein thrombosis (OVT) and renal vein thrombosis (RVT) after giving birth. The widespread development of thrombosis is treated for the first time in this study. Stasis, coagulation factor abnormalities, and intimal damage to the venous thrombosis risk can increase during pregnancy. It was mentioned that it diagnoses an abnormality in the hypercoagulability half of women with OVT. Despite the hypercoagulant abnormality observed in pregnant women, it was very unusual that the renal vein thrombosis led to this complication. It can lead to severe complication of OVT which can even cause death. It was the first time that the renal vein and ovarian vein thrombosis were observed in the postpartum period, and there was no coagulation abnormality. It is known that the thrombus in the postpartum period can be observed with the fever of unknown origin. The problematic, but rarely observed, postpartum disease such as ovarian venous thrombosis (OVT) is generally observed in the right ovarian vein. In this disease, avoiding the resulting laparotomy heparin and intravenous antibiotics is best solution for the patient. If it is to be noted a fever for unknown reasons, that it be thrombosis.